2016
DOI: 10.1016/j.jclepro.2016.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of water quality of municipal wastewater treatment plants in China: implications for resources utilization and management

Abstract: Influent and effluent quality of municipal wastewater treatment plants play significant roles in selecting the appropriate treatment technologies and influencing the ecology of receiving water bodies. The quality of reclaimed water sources for water reuse can also be determined based on the influent wastewater and treated effluent information. Comprehensive analyses based on statistical data collected from 3340 Chinese municipal wastewater treatment plants were performed so as to better understand the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(147 citation statements)
references
References 12 publications
3
142
1
1
Order By: Relevance
“…Na + +K + vs. Cl − (Figure 10c) of most waters were located below the equilibrium line, indicating that sodium and potassium ions were also affected by dissolution of salt rocks [45]. The HCO 3 − vs.…”
Section: Bivariate Plot and Dissolution Reactionmentioning
confidence: 98%
See 2 more Smart Citations
“…Na + +K + vs. Cl − (Figure 10c) of most waters were located below the equilibrium line, indicating that sodium and potassium ions were also affected by dissolution of salt rocks [45]. The HCO 3 − vs.…”
Section: Bivariate Plot and Dissolution Reactionmentioning
confidence: 98%
“…Beijing, the capital of China, has been confronted with severe water scarcity for the last 30 years. The annual average rainfall of Beijing is 584.7 mm, which is mainly concentrated from June to September [3]. The city's total water consumption was 3.82 billion m 3 in 2015, while the surface water resources were 932 million m 3 , and the gap was filled by excess use of groundwater [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other minority substances such as metal, toxic material, detergent, and bacteria (12,24,(26)(27)(28)(29). Huang (22) has investigated the characteristic of organic matters in domestic wastewater showed that fiber (20,64%) was the largest group of organic matters and followed by proteins (12,38%) and sugar (10,65%) were next largest.…”
Section: The Domestic Wastewater Characteristicsmentioning
confidence: 99%
“…Water resource is an important natural source for supporting and maintaining human health and social sustainable development [1]. Population growth, urban expansion, industrialization, consumption pattern, and energy structure changes result in the increased demand for freshwater resources [2].…”
Section: Introductionmentioning
confidence: 99%